2012
DOI: 10.1542/peds.2011-2079
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of 7-Year-Old Children Born at 32 to 35 Weeks’ Gestational Age

Abstract: Moderately preterm birth is associated with lower intelligence and poorer neuropsychological functioning at early school age. No differences in motor skills and verbal memory were found. Using gender-specific norms, our data suggest that moderately preterm boys catch up, whereas moderately preterm girls lag behind their peers on various neuropsychological functions by the age of 7 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 31 publications
7
60
0
1
Order By: Relevance
“…Similarly, no difference in attentional control was found in a cohort of 8-to 11-year-old children born moderate or late preterm (Odd et al, 2012). Although attention may increase with gestational age, other studies reported differences in attention for children born moderate or late preterm, while one study reported attentional differences at age 3 years but not at age 5 years for late preterm-born children (Caravale et al, 2005;Cserjesi et al, 2012;Mulder et al, 2009). ''executive function*'' AND ''multilingual* OR bilingual*'' AND ''infant* OR child*''…”
Section: Attentional Controlmentioning
confidence: 94%
See 4 more Smart Citations
“…Similarly, no difference in attentional control was found in a cohort of 8-to 11-year-old children born moderate or late preterm (Odd et al, 2012). Although attention may increase with gestational age, other studies reported differences in attention for children born moderate or late preterm, while one study reported attentional differences at age 3 years but not at age 5 years for late preterm-born children (Caravale et al, 2005;Cserjesi et al, 2012;Mulder et al, 2009). ''executive function*'' AND ''multilingual* OR bilingual*'' AND ''infant* OR child*''…”
Section: Attentional Controlmentioning
confidence: 94%
“…These deficits likely have long-term social and academic implications for the preterm population. Baron et al, 2012;Cserjesi et al, 2012;Edgin et al, 2008;Nosarti et al, 2007;Sun et al, 2009). Aarnoudse-Moens and colleagues (2012) suggest that deficits in response inhibition do not persist into middle childhood in children born < 30 weeks, but another study by Nosarti and colleagues (2007) reported significantly poorer performance on inhibitory tasks of adolescents at age 19 years born < 33 weeks.…”
Section: Executive Function and Prematuritymentioning
confidence: 99%
See 3 more Smart Citations